A morte é uma aula: o cemitério do Alecrim como referência viva da história de Natal-RN - Carneiro, Bartolomeu Silva (2022)
During my teaching experience in public and private schools in Natal-RN, I noticed that there is a significant difficulty to insert the students in the universe of discussions about the History and Historical Heritage of the city. This approach is almost always based on ignorance, inconsistencies of information and an apparent condition of lack of interest and absence of identity bond of the students with the theme. This finding was also present in reports shared with fellow teachers in the schools where I work and in the master's program. In face of this fact, when thinking about places that would enable the teaching of the city's history from its patrimonial condition, I chose the Alecrim Cemetery: an urban object with more than a century and a half of existence. Historically, the cemetery has already had its functional relevance questioned by the natalense society. However, nowadays, it is officially recognized as a local historical heritage and houses a considerable diversity of material and symbolic elements that can be identified, interpreted and classified as historical sources and memorial references of the city. This fact, together with a personal condition of interactions with the place, made me choose it as an adequate pedagogical tool to support the teaching of the History of Natal-RN and to awaken the students' interest in the city's history. In this sense, I propose, in this dissertation, to approach and re-signify sepulchral objects present in this urban necropolis in order to, from its historical and/or symbolic references, present and describe facts and aspects related to the history of the city of Natal-RN.